Clothing practices of selected adolescents with down syndrome - Billoso, Janielle Kale Bofill; Rayala, Maria Monica E. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Clothing practices and its influence on the development of one's self image and self esteem during the stage of adolescence has been proven to have a signifivant impact in the lives of individuals. This study dealt with the clothing practices of adolescents with Down Syndrome and how it could affect the individual's psychosocial wellbeing. The study described the clothing practices of selected adolescents with Down Syndrome in terms of their clothing acquisition (style, color, and comfort preferences and buying practices), use (grooming, and deciding on what to wear for specific occasions), and care. Thirty (30) respondents were gathered through a convenient non-probabilistic sampling method. respondents were selected from two organizations such as The Heart at Play Foundation, Inc. and the Down Syndrome Association of the Philippines Inc. The adolescents with assistance from their respective parents or guardians participated in the survey. Six of these adolescents ( along with their respective caregivers) were personally interviewed about their clothing practices. Data gathered from the survey were quantified and interpreted using descriptive statistics. Anecdotal data from the interviews conducted were used to verify and support the data gathered through the survey. The results of the study determined that the clothing practices of adolescents with Down Syndrome were not very different from the clothing practices of normal adolescents. There were merely some nuances that were unique to the respondents' clothing practices in terms of style influences and preferences, the impact of the decision making aspect in using and purchasing clothing, and the physical development that care and grooming practices aids them with. The research hopes to shed light on the persons with disabilities community and encourage more families with Down Syndrome members to use clothing practices as a tool to empower and include these individuals in our society.
Available to the general public.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman
Keywords: Clothing and dress -- Philippines -- Metro Manilla; Mentally ill teenagers -- Philippines -- Metro Manila -- Clothing; Clothing and dress -- Social aspects -- Philippines -- Metro Manila; Down syndrome -- Philippines -- Metro Manilla